Integration of Silicon and Printed Electronics for Rapid Diagnostic Disease Biosensing. Issue 2 (June 2016) - Thomas, Daniel J.; Tehrani, Zari
Abstract : Abstract: During this research, we developed a printed point-of-care device that was integrated with a biosensing silicon sensor. This resulted in the detection of a specific biomarker, which indicates the presence of a series of common diseases. The selective detection of biomarkers is an important component for early diagnosis. We fabricated an integrated device, which has inbuilt 200-μm-wide carbon printed electrical connections to a biosensor. This was found to be an essential component of making a noninvasive device. The present work describes the use of 3-dimensional printing fabrication techniques for producing a prototype point-of-care system made from aliphatic polyurethane polymer. During this research, the biosensor was selectively functionalized with antibodies. These results prove the concept of the specific and selective attachment of bioreceptor antibodies, which can subsequently be used for the detection of particular target biomolecules. The integration of carbon printed electronics as a critical component in the detection of disease provides a promising new route to rapid bioanalysis diagnosis.